Exploring Papua through Sabine Kuegler's Life Journey: A Travel Literature Analysis of Dschungelkind - Diyan Fatimatuz Zahro; Isti Haryati; Sri Megawati (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2026)
Despite the popularity of Sabine Kuegler’s novel Dschungelkind, little attention has been paid to how Papua and the Fayu tribe are represented and whether such representations reproduce or challenge colonial discourse. Therefore, this research aims to describe how Papua is portrayed in Sabine Kuegler’s novel Dschungelkind through Carl Thompson's Travel Writing framework. This study employed a qualitative descriptive method by analyzing textual data that explicitly or implicitly reflect the dimensions of reporting the world, revealing the self, and representing others. Data were collected through survey reading, focused reading, and verification reading, while reliability was ensured through both intrarater and interrater procedures. The findings reveal that this novel presents the world through both objective and subjective depictions. Objective depictions appear in descriptions of climate, flora, fauna, and food, whereas subjective depictions dominate descriptions of Papua’s landscapes, social interactions, health issues, and Fayu traditions. In the dimension of revealing the self, the author presents herself as a romantic self and shows her process of discovering the value of humanism within herself through her interactions with Papuan nature and the Fayu tribe. The representation of the other, the Fayu tribe (East) is not portrayed as inferior to Sabine (West). Instead, the novel adopts a cosmopolitan perspective characterized by empathy, awareness of equality, and the exchange of values. These findings suggest that Dschungelkind challenges conventional Eurocentric tendencies in travel literature and offers a more egalitarian framework for modern cross-cultural narratives.